17-3(w+5)=(w+5)-2w

Simple and best practice solution for 17-3(w+5)=(w+5)-2w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-3(w+5)=(w+5)-2w equation:


Simplifying
17 + -3(w + 5) = (w + 5) + -2w

Reorder the terms:
17 + -3(5 + w) = (w + 5) + -2w
17 + (5 * -3 + w * -3) = (w + 5) + -2w
17 + (-15 + -3w) = (w + 5) + -2w

Combine like terms: 17 + -15 = 2
2 + -3w = (w + 5) + -2w

Reorder the terms:
2 + -3w = (5 + w) + -2w

Remove parenthesis around (5 + w)
2 + -3w = 5 + w + -2w

Combine like terms: w + -2w = -1w
2 + -3w = 5 + -1w

Solving
2 + -3w = 5 + -1w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add 'w' to each side of the equation.
2 + -3w + w = 5 + -1w + w

Combine like terms: -3w + w = -2w
2 + -2w = 5 + -1w + w

Combine like terms: -1w + w = 0
2 + -2w = 5 + 0
2 + -2w = 5

Add '-2' to each side of the equation.
2 + -2 + -2w = 5 + -2

Combine like terms: 2 + -2 = 0
0 + -2w = 5 + -2
-2w = 5 + -2

Combine like terms: 5 + -2 = 3
-2w = 3

Divide each side by '-2'.
w = -1.5

Simplifying
w = -1.5

See similar equations:

| 51=3(3+2y) | | -4x+(-5x+21)=6 | | 8-5(7g-4)=98 | | 3(1+8r)=-165 | | log(y)=2.7 | | 6y+4=5y-3 | | 7x+4=2x+49 | | 7=(8x+5)+5 | | h+14=63 | | 223+334567.564383= | | r-15=16 | | 3y-10+y+54=8y+50-6y | | 5+2s+7=28 | | 12(80-x)=816 | | 2+5+x=3+4 | | 19-x-5=30 | | (25b-6)-8(3b+3)=-7 | | 8+3(-2n-7)=-(-5-3n) | | (x+4)(3x-24)=0 | | 7(b-5)=72 | | 18+-6g=-12g | | 3px(-3)=36 | | -2(-6x-4)=8x+2(x-2) | | 3(14+-5y)-5y=10 | | Y-15x=16 | | 2(1-x)+5=3(1+x)-8 | | -6(r+8)=-96 | | 5+3(-2g-7)=-40 | | -5-4p=27 | | y(2y+4)=77 | | x+15=65 | | -10-4p=22 |

Equations solver categories